Supervisi Akademik Pengawas Dalam Meningkatkan Kinerja Guru Raudhatul Athfal di Kabupaten Pidie - Yusnidar, Yusnidar; Marwan, Marwan; Bahri, Saiful (Jurnal Ragam Pengabdian, 2026)
This study aimed to analyze the implementation of supervisors’ academic supervision in improving teacher performance at Raudhatul Athfal Dayah Ulei Keuniree and Raudhatul Athfal Asy-Syarif in Pidie Regency. A descriptive qualitative approach was employed, involving eight participants comprising two supervisors, two principals, and four teachers. Data were collected through interviews, observations, and documentation and analyzed using the Miles, Huberman, and Saldaña model, supported by NVivo 15. The findings revealed that academic supervision was effectively implemented through four stages: planning, implementation, evaluation, and follow-up. Supervision was conducted regularly five times per semester through classroom observations, reviews of instructional administration, and constructive feedback. Although challenges such as limited time, administrative workload, and inadequate learning facilities were identified, the supervision process remained effective. Academic supervision contributed to improvements in lesson planning, instructional delivery, classroom management, teaching material development, learning assessment, and teacher professionalism. NVivo analysis indicated that teaching material development and lesson planning were the most prominent areas of improvement. Overall, the findings demonstrate that supervisors’ academic supervision plays a significant role in enhancing teacher performance at both Raudhatul Athfal institutions in Pidie Regency.